Cystamindi-ium tetrachlorocuprate [NH3(CH2)2SS(CH2)2NH3][CuCl4]: synthesis, crystal structure, and thermal decomposition. Issue 2 (11th March 2015) - Leshok, D. Y.; Golovnev, N. N.; Kirik, S. D.
<x content-type="archive" xml:space="preserve">Abstract</x> The salt [NH3(CH2)2SS(CH2)2NH3][CuCl4] was obtained by crystallization after adding CuCl2 to cystamine (Cysta), solved in hydrochloric acid. The assumption of conserved disulfide connection (S–S) in the compound, made on the basis of infrared spectroscopy, is further supported by the crystal structure determined from X-ray powder diffraction data. The compound has an ionic structure. [CuCl4]2− and CystaH22+ ions package in the form of inorganic and organic layers in the cell, interconnected through the formation of hydrogen bonds via NH3-groups and chlorine atoms of the complex [CuCl4]2−. Inorganic layers are additionally stabilized in the parquet package of [CuCl4]2− ions which provides a Cu-distorted octahedral coordination. CystaH2[CuCl4] is stable in air up to 200 °C. Thermal decomposition occurs in several stages, accompanied by breaking of S–S bonds, releasing of the organic component and yielding CuO.